Identifikasi Alkaloid Daun Kelor (Moringa Oleifera L) - Susilo Yulianto (Jurnal Kebidanan dan Kesehatan Tradisional, 2020)
Background: Indonesia has a lot of storing a variety of healthy plants and inhabited by various tribes with different traditional sanitary knowledge. Moringa leaf is a plant that is often used by the community to improve health. This type of research is an observational study that is to identify Moringa leaf alkaloid compounds. The purpose of this study was to identify the content of alkaloid compounds in moringa leaves which were arranged using tables and narratives. Methods: Descriptive observational research by extracting 260 grams of Moringa leaves, and identification in the laboratory. Results: The results of the identification of moringa leaf alkaloids using Wagner reagents contained brown sediment. Conclusion: The conclusion is positive Moringa leaves contain alkaloid compounds.